2015
DOI: 10.1007/s12603-015-0476-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress regulation as a link between executive function and pre-frailty in older adults

Abstract: Objectives Both pre-frailty and frailty are linked with impaired executive function (EF) but the mechanism underlying this relationship is not known. Williams and colleagues’ model posits EF affects health outcomes via stress regulation. This model was utlized to test indicators of stress regulation as mediators of the relationship between EF and pre-frailty in older adults. Design Cross-sectional. Setting Academic general clinical research centers. Participants 690 community-dwelling older adults ≥ 50 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For exploratory reasons, we also calculate the interaction of age and stress on executive performance. Old age shows adverse effects on executive functioning (review in Harada et al, 2013 ) and a recent study demonstrated that stress exposure and executive functioning were negatively related in older adults ( Roiland et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For exploratory reasons, we also calculate the interaction of age and stress on executive performance. Old age shows adverse effects on executive functioning (review in Harada et al, 2013 ) and a recent study demonstrated that stress exposure and executive functioning were negatively related in older adults ( Roiland et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous paper on renal function in these MIDUS participants found a significant age-related decline in glomerular filtration rate, but there were no individuals with Stage 4 or 5 Chronic Kidney Disease (41). Similarly, a recent study exploring executive function and indicators of frailty in 690 MIDUS participants, who were 50 years of age or older, found that only 17 met the frailty criteria posited by the Fried Frailty measure (42). Thus, despite multiple tests of physical functioning confirming age-related declines in performance (21,22,24), future research is needed to demonstrate that DHEA would be a robust correlate among already frail individuals.…”
Section: Discussionmentioning
confidence: 87%
“…Given the associations between EF and PNS functioning described heretofore, it is hypothesized that EF should predict physiological recovery from stressful events. Although evidence for this association is limited, preliminary research suggests that poorer EF is associated with longer heart-rate-recovery times from stress among older adults (Roiland, Lin, Phelan, & Chapman, 2015).…”
Section: Stress Recoverymentioning
confidence: 99%